Impact of an optical coherence tomography guided approach in acute coronary syndromes: A propensity matched analysis from the international FORMIDABLE‐CARDIOGROUP IV and USZ registry. Issue 2 (28th December 2016) - Iannaccone, Mario; D'Ascenzo, Fabrizio; Frangieh, Antonio H.; Niccoli, Giampaolo; Ugo, Fabrizio; Boccuzzi, Giacomo; Bertaina, Maurizio; Mancone, Massimo; Montefusco, Antonio; Amabile, Nicolas; Sardella, Gennaro; Motreff, Pascal; et al.
Abstract : Aim. To determine the potential clinical impact of OCT (Optical Coherence Tomography) during primary percutaneous coronary intervention in patients presenting with ACS (Acute Coronary Syndrome). Methods and Results. FORMIDABLE is a multicentre retrospective registry enrolling all patients presenting with ACS and treated with an OCT‐guided approach, while the USZ registry enrolled patients treated with a standard angiography guided approach. Multivariate adjustment was performed via a propensity score matching. The number stents useds was the primary outcome, while the incidence of MACE (a composite of death, myocardial infarction, target vessel revascularization, and stent thrombosis) was the secondary endpoint. A total of 285 patients OCT‐guided and 1, 547 angiography guided patients were enrolled, resulting in 270 for each cohort after propensity score with matching. Two stents were used in 12% versus 34%; 3 stents in 8% versus 38% of the patients ( P  < 0.001). After a follow up of 700 days (450–890), there was no difference in myocardial infarction (6% vs. 6%, P  = 0.86), while MACE (11% vs. 16%, P  = 0.06), target vessel revascularization (2% vs. 4%, P  = 0.15) and stent thrombosis rates (0% vs. 2.7%, P  = 0.26) were numerically lower for the OCT‐guided cohort but none of these endpoints did reach statistical significance. Conclusions. An OCT‐guided approach reduced the number of stents used, number of patients treated with more than one stent, while there was no statistically significant difference in clinical endpoints while most of them were numerically lower, including stent thrombosis rates. © 2016 Wiley Periodicals, Inc.